Design of an Integrated Aircraft Fuel Ordering Based on Blockchain Technology at an International Airport - Vikaliana, Resista; Rasyidiq, Fiqri (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
This study focuses on DPPU SHIPS. DPPU SHIPS is a subsidiary of PT Pertamina, which is a subsidiary of Pertamina that plays a role in the distribution and sale of aircraft fuel at Soekarno Hatta International Airport. Since 2020, Pertamina has been committed to digitizing all lines of business for efficiency. Therefore, the Digital Ground Operation (DGO) system was implemented, which combines the main business processes into one digital platform. In its implementation, weaknesses were found due to the absence of an integrated ordering system without intermediaries between airlines and Pertamina, resulting in a line of work that was prone to human error. This research aims to recommend an integrated service model for aircraft fuel distribution using blockchain technology. The booking system model is designed to ensure transparency of booking data and secure and valid receipt between airlines and Pertamina. Blockchain technology was chosen because it can guarantee transparency of orders, traceability, and the capacity to share information about the aircraft fuel distribution process.   Thus, the aviation fuel supply chain can be more reliable.  Furthermore, this technology can reduce human error in every transaction. The application of blockchain can revolutionize the way the supply chain works. This research consists of three stages: identifying the business processes of aviation fuel sales, identifying the data needed and used in each process along with the actors involved, and then formulating a model or design. The results of this research describe the model design of how the aircraft fuel ordering system is integrated by applying blockchain technology.